Use of Portable Electronic Assistive Technology to Improve Independent Job Performance of Young Adults with Intellectual Disability. Issue 3 (September 2014) - Collins, James C.; Ryan, Joseph B.; Katsiyannis, Antonis; Yell, Mitchell; Barrett, David E.
Poor employment outcomes for persons with intellectual disability (ID) persist despite legislative mandates designed to enhance access to gainful employment. Recent data suggest that only 37% of young adults with ID obtain paid employment outside of the home. Among those who do obtain employment, career options are limited and nearly half are paid below minimum wage. However, strategies such as the use of visual or auditory prompting to assist with task completion to improve employment outcomes may be provided by assistive technology (AT). The current study examined the use of readily available, inexpensive, and discrete portable electronic AT in an office setting to provide three unique modes of prompting and instruction (video, audio, and a combination of both) for three young adults with ID. Results revealed the AT was highly effective for increasing participants' ability to independently and correctly complete office-related tasks, yet the type of prompt that was provided had no effect on performance. Implications and suggestions for future research are provided.